Commerce to Culture: Understanding Islamic Values in Surakarta’s Traditional Markets and Tourism - Istijabatul Aliyah; Rara Sugiarti; Lintang Suminar; Eko Nursanty; Ratri Septina Saraswati (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2026)
Traditional markets are not only centers of commerce but also vital repositories of cultural heritage, playing a significant role in branding cities as unique heritage tourism destinations. This study explores the integration of Islamic values within traditional markets in Surakarta City and their impact on cultural tourism. Using a qualitative case study approach, the research examines how Islamic principles such as honesty, trustworthiness, and community support shape market practices and enhance tourists' cultural experiences. Focusing on key markets like Pasar Gedhe Harjonagoro, the findings reveal that these values not only influence vendor behavior but also contribute to the markets' appeal as cultural heritage sites. This study highlights the potential for traditional markets to serve as platforms for cultural exchange and sustainable tourism, emphasizing the importance of preserving local identity in a globalized world. The insights offered provide valuable guidance for stakeholders in tourism and cultural heritage preservation, demonstrating how Islamic values can be leveraged to promote sustainable tourism development.